La fosforescenza delle cose - Rambeau, Fréderic (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
This paper examines the relationship between subject and conscience in the works and thought of Gilles Deleuze. Starting from a comparison between Deleuze’s statements with those of phenomenology (Sartre, Husserl, Merleau-Ponty) and psychoanalysis (Lacan), the author shows how the French philosopher’s thought on the notion of subject is marked by a deep connection to pure immanence and transcendental field beyond the subject- object opposition. In Deleuzian ontology, the notion of subject, which shares a common ground with Lacanian subjectivation, is transformed and re-positioned as a «superject». As a unity of being and thought, brain and world, it is an individuation process which radically reshapes the very notion of subject as a part of cosmic speed that allows to grasp the being from within itself. Traduzione italiana a cura di Andrea Palumbo e Francesco della Noce. Revisione di Giulio Piatti